The Institutional Determinants of Internationalization: The Cases of Study Abroad Participation and International Student Enrollment - Marks, Jonathan; Yeager, Jr., Charles; Gatrell, Jay; Bennett, Jeremy (Journal of International Students, 2018)
Globalization, global citizenship, and cross-cultural competence are central to the mission of post-secondary institutions. In this paper, we examined study abroad participation rates and international student enrollments to understand the determinants that drive critical components of campus internationalization. We identified possible explanatory variables for study abroad participation and international student enrollment, conducting regression analyses to assess the relationships between variables. We found that several explanatory variables were significantly related to study abroad participation and international student enrollment. Models showed differences in how variables could be used to predict study abroad participation and international enrollment at different kinds of schools.